The Causes of Economic Growth - Szostak, Rick (Springer, 2017)
What are the causes of economic growth? As billions of people still live in poverty, this is perhaps the most important question in human science. It is also a very complex one, as rates of economic growth are influenced by a multitude of economic as well as political, geographical and sociological factors. This books attempts to advance a nuanced understanding of the process of economic growth by synthesizing the insights of several social science disciplines. Different theories and methods employed by economists and other social scientists to study the causes of economic growth are analyzed and it is shown how and why those insights should be integrated by applying best-practice techniques of interdisciplinary analysis. Scholars and practitioners are thus provided with a wide array of potential strategies for encouraging growth as well as guidance on how these strategies may interact.